CREDIT MANAGEMENT STRATEGIES AND FINANCIAL PERFORMANCE OF INDUSTRIAL GOODS SECTOR IN NIGERIA - Alhassan, Ismail; Islam, K. M. Anwarul (Indian Journal of Finance and Banking, 2021)
The influence of credit management methods on the liquidity and profitability of listed industrial goods firms in Nigeria was investigated in this study. It was decided to use a descriptive survey study design. The sample population for which copies of the questionnaire were distributed was 400 respondents, representing 65% of the population. The participants provided 355 valid responses, which were examined. For descriptive statistics, one-way ANOVA was utilized, and to test the hypotheses, a basic regression analysis method was applied. The results showed that the credit risk assessment, debt recovery strategy, and receivable collection policy sub-variables have a positive and statistically significant impact on the liquidity sub-variables - ability to pay, level of bad debt, and cash inflow. Liquidity had a positive and statistically significant effect on profitability. The study thus, suggest that companies in the industry should enhance their liquidity in order to achieve the targeted profit level by having effective credit terms and proper risk assessment strategy, designing and implementing debt recovery plans to aid collection of the overdue debt, adopting a stringent credit collection method, and employing and retained qualified accountants and credit administrators with excellent knowledge of credit control techniques. JEL Classification Codes: F65.